First occurrence of the Patagonian blennie, Eleginops maclovinus (Cuvier, 1830) and the silverside Odontesthes smitti (Lahille, 1929), in a temperate south-western Atlantic coastal lagoon - González Castro, Mariano (2013)
Among the fish that inhabit coastal areas of Patagonia (Argentina) is the Patagonian blennie, Eleginops maclovinus (Cuvier 1830) (Family Eleginopsidae) (Nelson, 2006), abundant in the southern region of South America and distributed throughout the Magellanic Biogeographic Province. It has been reported from Valparaiso, Chile to the San Matias Gulf in Argentina (Cousseau and Perrotta, 2004). Another species of Patagonian distribution is the silverside Odontesthes smitti (Lahille, 1929) (Family Atherinopsidae), which has been reported along the Atlantic Ocean coast from Uruguay (34°S) to Tierra del Fuego (54°S) and the Malvinas Islands (Dyer, 2000; Cousseau and Perrotta, 2004). This marine species inhabits only lower latitudes in July–August (winter) for reproductive purposes, as demonstrated by Macchi (1993) for the coast of Mar del Plata, Argentina. Mar Chiquita coastal lagoon (37°32′S–57°19′W) is a temperate, shallow estuary located in Buenos Aires province, Argentina. Separated from the sea by a littoral line of dunes, with an inlet joining it to the ocean of approximately 60 km2 and a maximum length of 25 km parallel to the sea (Fig. 1a), the Mar Chiquita lagoon is considered a World Reserve of Biosphere by the Coordination Council of the Man and Biosphere Program (MaB) of UNESCO. The lagoon receives fresh water from small streams, artificial channels and subterranean water. The salinity has a horizontal gradient and fluctuates between 0 and 36, depending on the tide and wind (Gonza´lez-Castro et al., 2009). One specimen of Eleginops maclovinus (Fig. 1b) and one individual of Odontesthes smitti (Fig. 1c) were recorded for the first time in the inlet channel (approximately 1200 m from the mouth) of Mar Chiquita coastal lagoon, Argentina (37°43′54′S–57°25′49′W) on 27 July and 05 July 2012, respectively. The occurrence of Eleginops maclovinus in Mar Chiquita lagoon so far represents the northernmost record for the species in the western Atlantic.